(untitled) (Journal of the College of Basic Education, 2023)
With the beginning of each academic year, there is a problem in preparing the schedule (class schedule), which requires skill in preparation and fairness in the distribution of lessons (classes). Therefore, there is a need for an effective program that contributes to the speedy completion of the establishment of the quota distribution schedule.